Dynamic Effects of Co-Ethnic Networks on Immigrants' Economic Success - Michele Battisti; Giovanni Peri; Agnese Romiti (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper investigates how the size of co-ethnic networks at the time of arrival affect the economic success of immigrants in Germany. Applying panel analysis with a large set of fixed effects and controls, we isolate the association between initial network size and long-run immigrant outcomes. We also look at those who were assigned to an initial location independently of their choice allows a causal interpretation of our estimates. We find that immigrants initially located in places with larger co-ethnic networks are more likely to be employed at first, but have a lower probability of investing in human capital.
Keywords: J24; J61; R23; 330; networks; immigration; human capital; employment